sensitivity experiment using CESM POP2 - Gu, Sifan (10722361); Liu, Zhengyu (8315514) (2021)
PD.nc for control experiment. PD_nowind.nc for an experiment in which the North Atlantic surface wind is suppressed to 1%. PD_FB.nc for the experiment in which the North Atlantic bottom topography is set to flat. PD_FB_nowind for the experiment in which the North Atlantic bottom topography is set to flat and the North Atlantic surface wind is suppressed to 1%.